Investigation of Anti-Toxocara Antibodies in Epileptic Patients and Comparison of Two Methods: ELISA and Western Blotting. (22nd April 2013) - Zibaei, Mohammad; Firoozeh, Farzaneh; Bahrami, Parviz; Sadjjadi, Seyed Mahmoud
Abstract : The relationship between Toxocara infection and epilepsy was previously demonstrated by several case-control studies and case reports. These previous studies were often based on the enzyme-linked immunosorbent assay (ELISA) using Toxocara excretory-secretory antigens, which are not specific due to cross-reactivity with other parasitic infections such as ascariasis, trichuriasis, and anisakiasis. An immunoblot analysis is highly specific and can detect low levels of Toxocara antibodies. Therefore, this assay may be useful in the identification of toxocariasis in epileptic patients. We examined patients who had epilepsy and healthy subjects for seropositivity for Toxocara infection by ELISA and Western blotting. Out of 85 epileptic patients, 10 (11.8%) and 3 (3.5%) persons exhibited Toxocara immunoglobulin G (IgG) antibodies responses by ELISA and by both techniques, respectively. Moreover, in the healthy group (n = 85 ), 3 (3.5%) persons were positive by ELISA, but none was detected by Western blotting. This study indicates that Toxocara infection is a risk factor for epilepsy in Iran. These findings strongly suggest the need to perform Western blotting immunodiagnosis, as well as the ELISA using Toxocara excretory-secretory antigens, to improve diagnosis of human toxocariasis in patients with epilepsy.